Impact of fecal short‐chain fatty acids on prognosis in critically ill patients. Issue 1 (25th August 2020) - Nakahori, Yasutaka; Shimizu, Kentaro; Ogura, Hiroshi; Asahara, Takashi; Osuka, Akinori; Yamano, Shuhei; Tasaki, Osamu; Kuwagata, Yasuyuki; Shimazu, Takeshi
Abstract : Aim: This study aimed to evaluate the relationship between fecal organic acids and mortality in critically ill patients. Methods: This retrospective study included 128 patients who fulfilled the criteria of systemic inflammatory response syndrome and had a serum C‐reactive protein level of greater than 10 mg/dL. Patients were treated in the intensive care unit for more than 2 days. Patients were divided into two groups: survivors and non‐survivors. We measured and compared eight kinds of fecal organic acids between the two groups. We focused on the minimum and maximum value of each fecal organic acid and evaluated prognostic factors by using classification and regression tree (CART) and multivariate logistic regression analyses. Results: We included 90 patients as survivors and 38 as non‐survivors. The CART analysis revealed that the dominant factors for mortality were the minimum values of propionate and acetate and the maximum values of lactate and formic acid. In the evaluation of the minimum values of fecal organic acids, propionate was significantly associated with increased mortality (odds ratio, 0.11 [95% confidence interval, 0.024–0.51]; P  = 0.005), acetate (0.047 [0.005–0.49]; P  = 0.01), and age (1.048 [1.015–1.083]; P  = 0.004). In the evaluation of the maximum values, lactate was significantly associated with increased mortality (5.21 [2.024–13.42], P  = 0.001) and age (1.050 [1.017–1.084]; P  = 0.003). Conclusion: An altered balance of fecal organic acids was significantly associated with mortality in critically ill patients. Abstract : This retrospective study aimed to evaluate the relationship between fecal organic acids and mortality in critically ill patients. The minimum values of fecal acetic acid and propionate in non‐survivors were significantly lower than in survivors. The altered balance of fecal organic acids was associated with mortality in critically ill patients.